Upaya Peningkatan Minat Baca Pada Anak Usia Dini Menggunakan Media Kartu Huruf Bergambar - Wahyati (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
This research is based on the problem of inadequate use of media in Early Childhood Education (PAUD) to increase interest in reading, resulting in a lack of enthusiasm and motivation for young children in carrying out reading activities. This research aims to describe how teachers make efforts to increase children's interest in reading using interesting and interactive media. Picture letter card media was chosen as an alternative to support children in carrying out reading activities. The method used is Classroom Action Research (PTK). There are three stages that must be carried out, namely planning, action, observation and reflection. The trial was carried out by 9 young children. After the trial was carried out, there was an increase in interest in reading, so that with the media of picture letter cards it could support and facilitate children in carrying out reading activities.